DOI: 10.1007/978-3-540-74549-5_76
|View full text |Cite
|
Sign up to set email alerts
|

Vitality Detection from Fingerprint Images: A Critical Survey

Abstract: Abstract. Although fingerprint verification systems reached a high degree of accuracy, it has been recently shown that they can be circumvented by "fake fingers", namely, fingerprint images coming from stamps reproducing an user fingerprint, which is processed as an "alive" one. Several methods have been proposed for facing with this problem, but the issue is far from a final solution. Since the problem is relevant both for the academic and the industrial communities, in this paper, we present a critical revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…In order to understand the motivation of organizing 80 such a competition, we observed that the first trials to face with this topic were often carried out with home-made data sets that were not publicly available, experimental protocols were not unique, and the same reported results were obtained on very small data sets. We pointed out these issues in [7].…”
mentioning
confidence: 95%
“…In order to understand the motivation of organizing 80 such a competition, we observed that the first trials to face with this topic were often carried out with home-made data sets that were not publicly available, experimental protocols were not unique, and the same reported results were obtained on very small data sets. We pointed out these issues in [7].…”
mentioning
confidence: 95%
“…The Fourier transform feature can quantify the difference in terms of high-frequency information loss for fake fingers. This approach is tested for a single scanner and silicon spoof material with average spoof/live EER of 2.4 % on a dataset of 720 fake and 720 live images from 36 individuals [6] and for gelatin and silicon with an average of 23 % EER for a dataset of 900 fake and 450 live images from 30 individuals [20].…”
Section: Characteristics Of Spoof and Live Imagesmentioning
confidence: 99%
“…In 2007 [6], a taxonomy is presented whereby methods are divided into software and hardware based. A similar division is suggested, but also consider an additional category where liveness is inherent to the biometric, i.e., it must be present in order to capture the biometric [2].…”
mentioning
confidence: 99%
“…Hardware-and software-based algorithms for the so-called fingerprint liveness detection have been already developed. The first survey on this topic is [8]. Several other approaches have been subsequently proposed [9], [10].…”
Section: Introductionmentioning
confidence: 97%